Estudos sobre a formação de professores de ciências no contexto da lei 10.639/03 - Souza, Ellen Pereira Lopes de (2014)
The issue of including contents of history and African-Brazilian and African culture in the curricula of primary school, determined by the law 10639/2003 has promoted discussions in the academic realm regarding ethnicity, diversity and race. Education is par excellence an opportunity for subjects to learn about the value of culture and maintain contacts with different cultural practices. In this way, the school is a relevant area in this process, but not always it occurs in the perspective of the respect for the cultural values and expressions of the subjects involved. Although Brazil is known worldwide for its pluri- and multi-cultural character, diversity is not always addressed in the classroom, although the school is composed of blacks, whites and indigenous. In this context, based on the assumptions of Dialectical Historical Materialism, this paper presents elements of a participating research, representing an educational activity for research and social action. The present study aims to investigate the knowledge mobilized by the teacher’s triad (trainer, in initial training and of basic education in continuing education) in the process of production and development of actions, which contribute to the critical training of teachers and students in relation to the historical origin of the Brazilian society, bringing reflections to understand how the proposed law has been applied, with the intention of expanding the dissemination of its proposals providing access to future analysis related to the topic. For data collection, semi-structured interviews were conducted with undergraduate degree students in the chemistry program, trainer teachers of education degree program in science of Higher Education of the state of Goiás, trainer teachers and coordinators of the courses of Sciences of Higher Education of the state of Goiás and leadership of social movement black in the state of Goiás. The interviews were recorded, transcribed, and data were grouped by units of meaning, and analyzed using the discourse analysis technique. The results indicate that this is an alternative that fulfills its educational role through dialogue with our peers, which occurred both in the Collective Black and during the interviews, and was a strategy to bring the discussion of the demand of the law (law 10639/2003) into the University in undergraduate courses in science and mathematics programs, through inferences about the relationship between the teaching of history and African-Brazilian and African culture and science education present in the theoretical framework and in discussions about the speech produced by respondents during interviews. Besides the scientific dissemination of the product of our work, made possible by the documentary Absent Principle: Law 10639/03 in Teacher Training, this is an initiative that aims to contribute to the discussion of the Law 10639/03 in teacher training courses, as well as and its social and cultural diffusion to the scientific community.